Equipoise, standard of care and consent: responding to the authorisation of new COVID-19 treatments in randomised controlled trials - Holm, Søren (Journal of medical ethics, 2023)
In response to the COVID-19 pandemic, large-scale research and pharmaceutical regulatory processes have proceeded at a dramatically increased pace with new and effective, evidence-based COVID-19 interventions rapidly making their way into the clinic. However, the swift generation of high-quality evidence and the efficient processing of regulatory authorisation have given rise to more specific and complex versions of well-known research ethics issues. In this paper, we identify three such issues by focusing on the authorisation of molnupiravir, a novel antiviral medicine aimed at reducing the ability of SARS-CoV-2 to multiply in the body, for clinical use by the National Health Service in England and the concomitant testing of molnupiravir through the large-scale Platform Adaptive trial of Novel antiviRals for eArly treatMent of COVID-19 In the Community randomised control trial. By analysing the ways in which the authorisation and clinical use of molnupiravir complicate standard approaches to clinical equipoise, standard of care and participant consent in the PANORAMIC randomised control trial, we will explain some of ethical implications for clinical trials that aim to study the efficacy and safety of new COVID-19 and other therapeutics when conditional authorisation has already been granted and when such treatments have already been made available to patients by national health providers.